ADMINISTRASI SARANA PENDIDIKAN DALAM MENINGKATKAN HASIL BELAJAR AKUNTANSI DI SMA ISLAM TELADAN PALEMBANG TAHUN PELAJARAN 2015/2016 - Yulaini, Erma (Graduate Program Magister Manajemen Pendidikan, 2018)
The problem of this research was how much the relation of administration of education facilities with the learning result of Accounting in SMA Islam Teladan Palembang in Academic Year 2015/2016. This study aimed at determining the relationship of educational facilities to Accounting learning outcomes in SMA Islam Teladan Palembang. The sample of research were 72 students, with two variables, the learning tool (independent variable) and Accounting learning result (dependent variable). Data collection techniques used documentation and questionnaire. Data were analyzed by quantitative descriptive, product moment and t-test. The results of this study obtained the value of rcount = 0.1802 based on interpretation table r value is expressed to have a level of relationship